Amino acid requirements of the infant: the amino acid composition of human breast milk - Moughan, Paul J.; Deglaire, Amelie; Yan, Yalu; Wescombe, Philip; Lim, Wen Xin Janice; Stroebinger, Natascha; Duan, Sufang; Szeto, Ignatius Man-Yau; Hodgkinson, Suzanne (Frontiers in Nutrition, 2024)
The recommended amino acid requirements of the infant are based on the amino acid composition of mature human breast milk. The amino acid composition of breast milk is usually determined following either acid or alkaline (for tryptophan) hydrolysis. For accuracy, however, the known effect of hydrolysis time on amino acid composition should be accounted for. Also, ideally the amino acid composition of breast milk should be given in units of digested (assumed to be absorbed) amino acids. A review of the literature is presented which gives mean total amino acid concentrations in mature human milk (n=26 studies), mean hydrolysis correction factors (n=3 studies) and mean true ileal amino acid digestibility coefficients (n=3 studies, suckling piglet). There were differences between the estimates of amino acid concentration corrected for hydrolysis time and digestibility, and current FAO (2013) recommendations that were not corrected for these factors. The values based on the published literature up until 2023 (mg/g true protein) corrected for hydrolysis time and digestibility gave higher values (more than 16% higher) for leucine, lysine and threonine, and considerably higher values (greater than 30%) for histidine and tryptophan. Current recommendations may need revision.